Implementation of Performance Management at Kurnia Supermarket Tanjungpinang City (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the implementation of performance management in Kurnia Supermarket, Tanjungpinang City. The type of research used is descriptive research with a qualitative approach. Data collection was carried out through observation and in-depth interviews. The sample used was purposive sampling. The informants are 3 people, namely 1 manager and 2 employees from the goods arrangement staff and cashier division, in order to obtain a comprehensive perspective related to the implementation of performance management implemented. The results of the study show that performance management at Kurnia Supermarket has been implemented well. This is reflected in the implementation of clear goal setting, achievement of performance targets, and employee competency development that focuses on improving work quality. This implementation also supports the improvement of operational efficiency which has a positive impact on the company's overall performance. Although it has shown positive results, the study also found several challenges, such as a lack of understanding of some employees regarding the performance management system and limited human resources in some divisions. Therefore, it is recommended to improve communication and increase socialization about performance management to all employees to achieve more optimal results.